2020
DOI: 10.1088/1755-1315/421/8/082026
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological survey of ringworm outbreak in cat shelter

Abstract: Dermatophytosis (ringworm) is the most important infectious and contagious skin disease of cats in shelters. Wherein, the diagnosis, identification and treatment of dermatophytosis is not always effective. Here we report an epidemiological study of the outbreak of feline dermatophytosis in animal shelter in Moscow region. At least 11% of cats kept in the shelter were affected. Seventeen cats suspected dermatophytosis were isolated for mycological examination and treatment, 82% of them were culture-positive. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Based on the age of the sampled animals, the prevalence of feline dermatophytosis in this study from the highest to the lowest was 36/181 (19.9%) for cats younger than one year, 9/136 (6.6%) for cats between one and three years of age, and 7/111 (6.3%) for cats older than three years of age (Table 2). As reported by [17], 11/17 (64.7%) of dermatophytepositive cats were younger than one year, while [3,18] reported that cats aged 6 months and younger were more likely to have greater prevalence. Increased susceptibility to dermatophytosis in kittens can be impaired by a variety of causes, including immaturity of the immune system, insufficiency of past immunity, skin micro trauma induced by siblings or ectoparasites, and frequent close contact with other cats during socialization [3,17].…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…Based on the age of the sampled animals, the prevalence of feline dermatophytosis in this study from the highest to the lowest was 36/181 (19.9%) for cats younger than one year, 9/136 (6.6%) for cats between one and three years of age, and 7/111 (6.3%) for cats older than three years of age (Table 2). As reported by [17], 11/17 (64.7%) of dermatophytepositive cats were younger than one year, while [3,18] reported that cats aged 6 months and younger were more likely to have greater prevalence. Increased susceptibility to dermatophytosis in kittens can be impaired by a variety of causes, including immaturity of the immune system, insufficiency of past immunity, skin micro trauma induced by siblings or ectoparasites, and frequent close contact with other cats during socialization [3,17].…”
Section: Resultsmentioning
confidence: 89%
“…As reported by [17], 11/17 (64.7%) of dermatophytepositive cats were younger than one year, while [3,18] reported that cats aged 6 months and younger were more likely to have greater prevalence. Increased susceptibility to dermatophytosis in kittens can be impaired by a variety of causes, including immaturity of the immune system, insufficiency of past immunity, skin micro trauma induced by siblings or ectoparasites, and frequent close contact with other cats during socialization [3,17]. The present study found a moderately higher incidence of dermatophytes (13.4%) in female cats than in male cats (10.7%), as compared to a study in Eastern India that recorded a higher prevalence of male cats than female cats and the disparity in prevalence between female and male cats may be due to unequal number of samples of each sex [7].…”
Section: Resultsmentioning
confidence: 89%